2008
DOI: 10.1002/micr.20472
|View full text |Cite
|
Sign up to set email alerts
|

The epineural sleeve technique for nerve graft reconstruction enhances nerve recovery

Abstract: The purpose of the study was evaluation of nerve recovery following epineural sleeve technique for graft reconstruction in rat sciatic nerve. This technique provides the epineural sleeve to cover and separate the site of coaptation. Animals were divided into three groups: CNG-conventional nerve grafting, ESN-epineural sleeve from recipient nerve stumps, ESG-epineural sleeve from graft. Nerve regeneration was evaluated by pin-prick, toe-spread test, walking track analysis and somatosensory-evoked potentials (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
2
18
0
1
Order By: Relevance
“…The histological analysis showed regeneration of small nerve fibers, and the inside-out slided epineural tube did not show degeneration or scarring. Histologically, a structure resembling epineurium was formed on the donor site, which corresponds with the findings of previous studies in which the epineurium was removed 18,31,37 ( Figure 3). The formation of small nerve bundles, microfascicular regeneration, is a known phenomenon after nerve transection or ischemic injury, as is the regrowing of these microfascicles outside the nerve trunk.…”
Section: Discussionsupporting
confidence: 89%
“…The histological analysis showed regeneration of small nerve fibers, and the inside-out slided epineural tube did not show degeneration or scarring. Histologically, a structure resembling epineurium was formed on the donor site, which corresponds with the findings of previous studies in which the epineurium was removed 18,31,37 ( Figure 3). The formation of small nerve bundles, microfascicular regeneration, is a known phenomenon after nerve transection or ischemic injury, as is the regrowing of these microfascicles outside the nerve trunk.…”
Section: Discussionsupporting
confidence: 89%
“…Lubiatowski et al 24 compared the nerve recovery following epineural sleeve technique with graft reconstruction in rat sciatic nerve transection model. They reported that nerve defects repaired with the sleeve technique to anchor nerve grafts displayed improved functional recovery when compared with the conventional epineural repair.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,24 In our experiment, a 10-mm defect was created, and the epineurium from the proximal stump was mobilized preserving only 2 mm, and it was reversed to facilitate gap bridging. In contrast to the above-mentioned studies, 8,9,23,24 our laboratory has selected the rabbit sciatic nerve transection model, because it has a well-developed epineurium, which can be harvested without significantly injuring the nerve. 21 Moreover, the complications of automutilation and autotomy seen with the rat sciatic nerve injury model are completely avoided.…”
Section: Discussionmentioning
confidence: 99%
“…The graft was coaptated proximally to the sciatic nerve and distally to the posterior tibial nerve using six 10/0 nylon sutures (Bear Microsurgery, Arosurigcal instruments, Newport Beach) creating a “pull‐over sleeve,” which was first described by Siemionow and coworkers26, 27 The muscle was closed using 4 5/0 Vicryl sutures (Ethicon Inc, Johnson & Johnson Somerville), followed by closing the skin using 5/0 Vicryl sutures (Ethicon Inc, Johnson & Johnson Somerville).…”
Section: Methodsmentioning
confidence: 99%